Implementation Of Compensation In Land Procurement For The Construction Of Bengkulu-Tabapenanjung Toll Road - Kholilurrohman Kholilurrohman; Rosmanila Rosmanila; Uswatun Hasanah; Desy Maryani (JURNAL HUKUM SEHASEN, 2024)
The results showed that the implementation of the consignment began with the formation of a land acquisition committee whose job was to see and assess the amount of compensation for land acquisition based on the NJOP and consignment. This can be done if the community receives a large amount of compensation and can collect it at the Argamakmur District Court by bringing ownership documents. In this study, what is called land acquisition is an activity of providing land by providing proper and fair compensation. Where compensation must first go through a committee and the NJOP will assess how much compensation will be given in accordance with the land owned by the community. So that when the compensation given is agreed upon, it is possible to bring the ownership documents to the Argamakmur District Court.